Sustainable Development – unbalanced devastation of the environment and its consequences - Sztumski, Wiesław (Problemy Ekorozwoju, 2014)
The article contains a reflection on the role of the idea of sustainable development in supporting the existence of human species. The problem is not easy and raises many questions. The contemporary social context does not favor sustainable development. Firstly, it is too firmly rooted in anthropocentrism, which is supported by the religion, and by the traditional European philosophy. Both make people think more about heaven than about the Earth. Thus, people are focused more on the soul than on the body; they are caring more for the favor of God than for their environment. Secondly, the ideology of consumptionism transforms people into wasters who increasingly over-exploit the Earth’s resources. Thirdly, people – the social masses and the ruling elites – intensely stupefied, are not driven by reason or intellect. That is why, there is little hope that the degradation of environment will be stopped and future generations will be given the chance to survive as a result of the implementation of the idea of sustainable development.